Pengembangan Produk Lifestyle Berfitur Menghibur Dengan Teknologi CNC Bagi Komunitas Kreatif Cirebon - Deny Willy Junaidy; Linda Mawali; Siti Sa’adah; Samuel Aswin Moeljanto; Sarif Gunawan (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2022)
Our community service is to develop some lifestyle products with contemporary-entertaining features by means of CNC technology application towards Cirebon Creative Community. This activity involved academician, designer-entrepreneur, village activist, as well as students joining Independent Campus Learning Program (MBKM). The 6 months training has produced new product development as well as skills, methods of product development, market introduction. The product development process emphasizes the use of Computer Numeric Control (CNC) technology. CNC technology was applied mainly for material cutting and 3-Dimensional contouring. The program finally came up 6 leather bags with new features of metal and wood locking mechanics that provide an entertaining effect. The six products have been officially registered of Industrial Design Copyright at the Directorate General of Intellectual Property (DJKI). In the future, this product development will be included in the exhibitions and is expected to to tap a new market niche in today's modern market.